Acute inflammatory responses induced by flexibility training with two different intensities - Nogueira,Carlos José (2022)
ABSTRACT This research analysed the acute effects of flexibility training with two different intensities on inflammation. Twenty-eight young military personnel males were randomised into two groups of 14 individuals each: Submaximal Stretching Group (SG) and Maximal Stretching Group (MG). The training routines were applied for each group and involved shoulder horizontal flexion, shoulder horizontal extension, hip flexion and hip extension. Basal blood samples were collected immediately after exercise and 24 h later in order to assess the inflammatory markers (CRP, IL-6, IL-10). Repeated measures ANOVA (2x3) for intragroup and intergroup comparisons with the adjusted Bonferroni post-hoc test was used. There was significant intergroup interaction (p< 0.05) with post-exercise CRP levels, which were significantly higher in the MG when compared to the SG (p= 0.035; Δ= 94%). There were no significant differences in IL-6 and IL-10 concentrations at any intergroup moment. The intragroup comparison showed a significant rise in IL-6 immediately after and 24 h after maximal stretching, with a significant difference (p< 0.05) 24 h after when compared to baseline (p= 0.008; Δ= 44.16%). These results suggest that maximal stretching promoted a higher acute inflammatory response when compared to submaximal stretching due to the greater intensity of the exercises.